2017
DOI: 10.4025/actasciagron.v39i3.32612
|View full text |Cite
|
Sign up to set email alerts
|

<b>Identification of QTL underlying agronomic, morphological and physiological traits in barley under rainfed conditions using SNP markers

Abstract: ABSTRACT. Barley (Hordeum vulgare L.) is considered a good genetic model for evaluating mechanisms of drought tolerance, and it is the most important threat to crop production worldwide. This study aimed to identify single-nucleotide polymorphisms (SNPs) associated with agronomic, morphological and physiological traits in a population of 137 recombinant chromosome substitution lines (RCSL) of barley, which were evaluated under rainfed conditions, in Cauquenes, southern Chile (35°58' S, 72°17' W). The annual pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
(72 reference statements)
1
5
0
Order By: Relevance
“…They detected trait-reducing effects in the same chromosomal region on 7H where the effects in this study were mapped. QTL effects on 2H, 4H, and 7H were also detected by Arriagada et al [ 42 ] and Mora at al. [ 43 ].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…They detected trait-reducing effects in the same chromosomal region on 7H where the effects in this study were mapped. QTL effects on 2H, 4H, and 7H were also detected by Arriagada et al [ 42 ] and Mora at al. [ 43 ].…”
Section: Discussionsupporting
confidence: 72%
“…They detected QTL for biomass yield on chromosomes 2H and 6H. Arriagada et al [ 42 ] and Mora et al [ 43 ] tested 137 barley recombinant chromosome substitution lines, derived from a cross between wild barley accession Caeserea 26–24 and malting barley Harrington, in Mediterranean environments in Chile under rain fed conditions. They detected QTL for biomass on 2H, 5H, and 7H.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the negative effects of drought could be overcome by the identification and use of drought-tolerant varieties (Van Oosten et al, 2016). Given this solution, the dissection of molecular mechanisms that underlie adaptive traits represents one approach to understanding stress tolerance in plants (Budak et al, 2015;Liu et al, 2017;Arriagada et al, 2017). For example, Merchuk-Ovnat et al (2016) showed that the introgression of QTLs on chromosomes 1B and 2B of T. turgidum into T. aestivum can enhance drought tolerance in domesticated wheat.…”
Section: Introductionmentioning
confidence: 99%
“…In order to sustain normal growth in drought condition, the plant increase water use efficiency (Liu et al, 2015;Arriagada et al, 2017). Plant water status affects photosynthesis process, plant growth, development, and yield (Arriagada et al, 2017).…”
Section: Flag Leaf Width (Flw)mentioning
confidence: 99%
“…In order to sustain normal growth in drought condition, the plant increase water use efficiency (Liu et al, 2015;Arriagada et al, 2017). Plant water status affects photosynthesis process, plant growth, development, and yield (Arriagada et al, 2017). One of the important criteria has been widely used to explain plant water status in barley is flag leaf RWC (Liu et al, 2015;Forster et al, 2004).…”
Section: Flag Leaf Width (Flw)mentioning
confidence: 99%